2019
DOI: 10.1111/age.12858
|View full text |Cite
|
Sign up to set email alerts
|

Old World camels in a modern world – a balancing act between conservation and genetic improvement

Abstract: Old World camels have served humans in cross-continental caravans, transporting people and goods, connecting different cultures and providing milk, meat, wool and draught since their domestication around 3000-6000 years ago. In a world of modern transport and fast connectivity, these beasts of burden seem to be out-dated. However, a growing demand for sustainable milk and meat production, especially in countries affected by climate change and increasing desertification, brings dromedaries (Camelus dromedarius)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 86 publications
4
61
0
5
Order By: Relevance
“…The trend of Ne shows a bottleneck around 2000-6000 years ago in Iranian central desert dromedary camels. This is consistent with a decline in Ne in Old World camels around 4000-5000 years ago and might be related to the domestication scenarios of dromedary and Bactrian camels [2].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The trend of Ne shows a bottleneck around 2000-6000 years ago in Iranian central desert dromedary camels. This is consistent with a decline in Ne in Old World camels around 4000-5000 years ago and might be related to the domestication scenarios of dromedary and Bactrian camels [2].…”
Section: Discussionsupporting
confidence: 85%
“…Camelini (one-and two-humped camels) and Lamini (New World camels) are two tribes of the Camelidae family [1]. Camelids influence human endurance and thriving in the peripheral agro-natural zones of (semi-) deserts [2]. Today, camels have gained significance as sustainable livestock species with certain important properties (e.g., immunogenic and milk composition) [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this study nucleotides sequences of 12S rRNA and cox1 genes of the microfilariae revealed a high similarity with O. fasciata from Bactrian camels in China (Gen-Bank: JQ316672). Based on the hypothesis of Onchocerca species evolution, Africa has been suggested as the origin of O. fasciata [37]; however, divergence and domestication of Bactrian camels took place earlier in history than one-humped dromedaries [45]. Hence Bactrian camels could have acquired the infection from dromedaries through the historical network of trade caravan routes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Rigorous pedigree recording, combined with permanent camel identification, are therefore better tools to clearly identify individual hybrids and the exact genetic contributions of dromedary and Bactrian camel to their genetic make-up. The increasing availability of advanced techniques for genetic and parentage testing will allow a better understanding of the genetics of dromedary, Bactrian camel, and their hybrids, possibly permitting the detection of valuable genetic traits related to increased productivity or adaptability (Burger et al 2019). Explanatory notes: Hump area-8, Bactrian humps; 7, two well-developed humps closer than in the Bactrian but separate at their base; 6, two well-developed humps with their bases touching each other; 5, one large hump with two symmetric small humps at the apex; 4, one large hump with two asymmetric small humps at the apex, the rear hump bigger than the front one; 3, one large hump with two visible mounds at the apex; 2, one large hump with a clear depression several centimetres deep on the front top margin; 1, dromedary hump.…”
Section: Overview Of Main Established Hybrid Advantagesmentioning
confidence: 99%